Banana Blossom as a Novel Ingredient in The Zero Waste Strategy: Application in Flakes - Rahmadhia, Safinta Nurindra; Sari, Meta; Wahyudi, Maulidya Eka; Ibdal; Fitriani, Aprilia; Jebreen, Ali (Universitas Ahmad Dahlan, 2025)
Banana bud is an underutilized byproduct of the banana plant. Banana bud is rich in fiber and macronutrients that promote health. The potential of banana bud can be optimized by transforming it into convenient ready-to-eat food products. This study was contributed to facilitate the conversion of agricultural waste into nutrient-dense functional foods. This investigation will involve the preparation of flakes using banana bud flour and arrowroot flour as substitutes for wheat flour. Each mixture incorporated banana bud and arrowroot flour at concentrations of 5%, 10%, and 15%. Additionally, the flakes will undergo assessment of their chemical, physical, and sensory characteristics. The incorporation of banana bud and arrowroot flour into the flakes resulted in a considerable increase in total protein and crude fiber values compared to the control sample. The hardness and crunchiness of the flakes varied considerably, although the water absorption capacity rose markedly. The incorporation of banana bud flour resulted in the flakes acquiring a reddish hue. The outcomes of the descriptive sensory evaluation yielded an assessment of color, odor, texture, flavor, aftertaste, and texture after rehydration conducted by the panellists. The study's results indicate that banana plant waste can be utilized to produce nutrient-dense food products favored by panellists.